The Role of E-Commerce in Encouraging the Indonesian Economy during the Covid-19 Epidemic as a Form of Modern Entrepreneurship - Wirastomo, Jizenji Tyas; Handayani, Langgeng Sri; Alim, Syahrul (Jurnal Ilmiah Global Education, 2024)
The number of sectors in online business makes business actors who want to invest need to guess what online businesses are popular and profitable in the current era of the COVID-19 pandemic, such as e-commerce, edutech and health. startup business sectors, precisely because of this pandemic, experienced a significant increase in business where online health platforms such as Halodoc became popular because they helped the public who only wanted to consult and diagnose health online. The e-commerce business is also a major need for the public in transacting on during this pandemic, considering that people are afraid to shop directly so that purchases of some necessities are made online through e-commerce platforms. In addition to the well-established national e-commerce business platforms, local e-commerce platforms are also emerging, especially to meet basic needs. Young people in several cities create local e-commerce platforms to help the process of buying goods from consumers to the market. Next, there are startup business collaboration tools, such as the Zoom and GotoMeeting applications, which have become popular in the era of the COVID-19 pandemic. Foreign companies have taken opportunities in this sector, considering that there are still few or no players taking advantage of the collaboration tools startup business. People are increasingly avoiding public places and offline retail stores, so online sales for some sectors are increasing. Reporting from neilpatel.com, conversions for the food, health and pharmaceutical sectors increased significantly. The food sector experienced an increase of 55%, health 19%, and pharmaceuticals 11%. In the United States alone, online sales are predicted to increase by up to 12% of their total spending in 2020. From these results, it can be concluded that behind the many benefits of online e-commerce business, there are still many impacts for other offline businessmen who do not use media. social as a means of business.